THE DEVELOPMENT OF E-MODULE STATISTIC COURSE IN BUILDING ENGINEERING EDUCATION STUDY PROGRAM: IN STATE UNIVERSITY OF JAKARTA - Haryati Dewi Lastari; R. Eka Murtinugraha; Riyan Arthur (Jurusan Pendidikan Teknologi Dan Kejuruan, 2021)
This study aims to develop teaching materials based on electronic modules in the Statistics subject in the Building Engineering Education Study Program, State University of Jakarta that can assist lecturers in delivering course material and make it easier for students to understand the subject matter. The method used in this research is research and development (R&D) with the development model used is ADDIE. (1) Analysis, (2) Define, (3) Develop, (4) Implementation, (5) Evaluation. This study uses a questionnaire as a tool to test the feasibility of a product by media expert validators and material experts. Product developed is electronic modules consists of 7 material. The results of validation by media experts get an average percentage of 87% in the